If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1 + 2 = 6 Reorder the terms: -1 + 2 + 4x = 6 Combine like terms: -1 + 2 = 1 1 + 4x = 6 Solving 1 + 4x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4x = 6 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 6 + -1 4x = 6 + -1 Combine like terms: 6 + -1 = 5 4x = 5 Divide each side by '4'. x = 1.25 Simplifying x = 1.25
| 2=13/9+b | | 2=9+b/13 | | 7(8-2b)= | | 8x+27x-9=7(5x+8) | | 3x+2x+9=14 | | 3b^2-18b=b-6 | | 3x+32x-2=7(5x+2) | | 2x^2+2x-25=0 | | -4=r/9-5 | | 3.45+3X=2.1 | | 4x-1=-4+4x | | 6X-25=5 | | 2-6x+36=0 | | 7(2r-4)-7r=7r-28 | | 6-4m=6-9m | | log(4)64=4x-3 | | -4.9x^2+9.9x-5=0 | | -4.9x^2+20x-5=0 | | 5(x-4)+6=-14 | | c=-a+2 | | 5m-3=-3+5m | | F-3.3f= | | u^2+2u+1= | | 8a+c=-7c+16 | | 2g+7=5g-2 | | 2x^2+8x+8=72 | | x^2+11x-30= | | 8-7r=r-16 | | 2x-7=6x+7 | | 0.50x+0.20(130)=0.25(36) | | -3x+4=2 | | 2x^2-6=25 |